2017
DOI: 10.1042/bcj20170281
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic disorder in the partitioning protein KorB persists after co-operative complex formation with operator DNA and KorA

Abstract: The ParB protein, KorB, from the RK2 plasmid is required for DNA partitioning and transcriptional repression. It acts co-operatively with other proteins, including the repressor KorA. Like many multifunctional proteins, KorB contains regions of intrinsically disordered structure, existing in a large ensemble of interconverting conformations. Using NMR spectroscopy, circular dichroism and small-angle neutron scattering, we studied KorB selectively within its binary complexes with KorA and DNA, and within the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Such affinity is relatively small, but it allows a proper regulation of the several pathways where NUPR1 is involved (18), achieving a high specificity despite a moderate binding energy. Moderate affinities (i.e., in the range 1-10 M) are not rare for other IDPs, and they have been measured during the formation of "fuzzy" complexes, where the partners remain disordered after complex formation (75,76); these fuzzy complexes facilitate fast binding since no disorder-to-order transition is happening.…”
Section: Energetic and Thermodynamic Determinants Of The Peptide/nuprmentioning
confidence: 99%
“…Such affinity is relatively small, but it allows a proper regulation of the several pathways where NUPR1 is involved (18), achieving a high specificity despite a moderate binding energy. Moderate affinities (i.e., in the range 1-10 M) are not rare for other IDPs, and they have been measured during the formation of "fuzzy" complexes, where the partners remain disordered after complex formation (75,76); these fuzzy complexes facilitate fast binding since no disorder-to-order transition is happening.…”
Section: Energetic and Thermodynamic Determinants Of The Peptide/nuprmentioning
confidence: 99%
“…Option Aii could still contribute as a part of mechanism Bi, in which the centromere indirectly sequesters most of the diffusible ParB in a single conformer population through selective attraction of spontaneously arising active dimers. The intrinsically disordered nature of ParB Nter domains implies that they exist as a number of metastable, interchangeable conformers of which only one or a minority can spread, as underlined by the recent study of Hyde et al [37], lending plausibility to mechanism Bi. However, if this proposal held, the SopB N15/F protein should assemble visible complexes with bound N15…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, Surtees & Funnell [7] observed oligomerization of P1 ParB N-terminal domains in the absence of parS in vitro and in yeast, and Hyde et al [37] concluded that specific binding of KorB did not reduce intrinsic disorder but rather selected from a population of natural conformers. We report here our attempts to observe spreading of ParBs fused to non-parS DNAbinding proteins, and to distinguish ParB-parS binding from ParB-ParB interaction as the basis for conversion to spreading competence.…”
Section: Introductionmentioning
confidence: 99%
“…(Fig 1) On one hand there are indications that the properties of ParBs do change in response to centromere binding: F SopB and P1 ParB co-repressor activity is stimulated in trans by sopC and parS respectively [33,34], SopB-mediated stimulation of SopA ATP hydrolysis is enhanced by sopC [35] and a newly-discovered CTPase activity exhibited by some ParB proteins, including SopB, is enhanced by centromere binding [36,37]. On the other hand, Surtees & Funnell [7] observed oligomerization of P1 ParB N-terminal domains in the absence of parS in vitro and in yeast, and Hyde et al [38] concluded that specific binding of KorB did not reduce intrinsic disorder but rather selected from a population of natural conformers.…”
Section: Introductionmentioning
confidence: 99%